Economic Valuation of Cinnamon (Cinnamomum burmannii Blume) Utilization in Several Villages of Kutapanjang District, Gayo Lues Regency - Ridwan; Linda, Maya; Handayani, Triaty; Arabia, Teti (Jurnal Hutan dan Masyarakat, 2025)
Cinnamon (Cinnamomum burmannii Blume) is one of the high-value crops cultivated by local communities in Gayo Lues Regency, Aceh. The bark of the cinnamon plant provides significant economic benefits and contributes substantially to household income. This study aims to (1) determine the economic value of cinnamon bark utilized by local farmers and (2) analyze its contribution to household income compared to other livelihood activities. Data were obtained through interviews with 60 respondents from Ulun Tanoh, Rema Tue, Tampeng, and Kutapanjang Villages in Kutapanjang Subdistrict. The research applied a descriptive quantitative approach focusing on the economic value of cinnamon bark. The results show that the average annual income from cinnamon bark reached IDR 13,499,683 (IDR 1,124,974 per month), contributing 60.6% of total household income. The 60.9% contribution of cinnamon indicates that cinnamon farming provides 1.5 times higher income than secondary activities, emphasizing its vital economic role in supporting rural livelihoods.